The Relationship between Religious Attitudes and Perseverance in Learning in Islamic Religious Education Lessons in Junior High Schools - Alimni, Alimni; Amin, Alfauzan; Kurniawan, Dwi Agus; Perdana, Rahmat; Pratama, Wahyu Adi; Triani, Elza (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This study aims to determine the relationship between religious attitudes and learning perseverance of students of SMP 1 Bengkulu City and SMP 1 Jambi City on the subject of Islamic Religious Education. Design/methods/approach – The research design is an associative quantitative research method with a correlational research design. The number of samples of junior high school students studied amounted to 140. Findings – It was found that the results of the T-test and the correlation test showed a significant comparison and there was a relationship between Attitude and Perseverance in Student Learning of SMP 1 Bengkulu City and SMP 1 Jambi City on Islamic Religious Education Subjects. Research implications/limitations – The implication of this research is that it can be used as a reference in taking follow-up actions in solving problems regarding the religious character of students and students' perseverance in learning. The author realizes that this study still has shortcomings, such as the sample used is only 2 schools and 2 different cities. The variables studied in this study were only variables of Religious Attitude and Student Learning Diligence in Islamic Religious Education subjects. In addition, there are many other indicators that have not been used. Originality/value – This research is expected to be used by educators as a reference regarding the relationship between religious attitudes and students' persistence in learning, especially in the subject of Islamic Religious Education.